2018
DOI: 10.1080/2162402x.2018.1466016
|View full text |Cite
|
Sign up to set email alerts
|

A novel bispecific antibody for EGFR-directed blockade of the PD-1/PD-L1 immune checkpoint

Abstract: PD-L1-blocking antibodies produce significant clinical benefit in selected cancer patients by reactivating functionally-impaired antigen-experienced anticancer T cells. However, the efficacy of current PD-L1-blocking antibodies is potentially reduced by ‘on-target/off-tumor’ binding to PD-L1 widely expressed on normal cells. This lack of tumor selectivity may induce a generalized activation of all antigen-experienced T cells which may explain the frequent occurrence of autoimmune-related adverse events during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 37 publications
(42 reference statements)
1
50
0
Order By: Relevance
“…Also noteworthy is a growing body of research focused on novel tumor-restricted immunotherapy strategies beyond the scope of this review. These promising approaches include: (i) Vaccines targeting neoantigens [259][260][261] ; (ii) Chimeric antigen receptor (CAR) T-cell therapy 262 ; (iii) Improved delivery of checkpoint blockade antibodies within the TME; (iv) Bispecific antibodies [263][264][265] ; and (v) Molecular shields restricting local activity of checkpoint inhibitors. 266 For future research, we propose studies designed to identify novel regulatory molecules that, when targeted, simultaneously enhance anti-tumor immunity yet suppress autoimmunity.…”
Section: Resultsmentioning
confidence: 99%
“…Also noteworthy is a growing body of research focused on novel tumor-restricted immunotherapy strategies beyond the scope of this review. These promising approaches include: (i) Vaccines targeting neoantigens [259][260][261] ; (ii) Chimeric antigen receptor (CAR) T-cell therapy 262 ; (iii) Improved delivery of checkpoint blockade antibodies within the TME; (iv) Bispecific antibodies [263][264][265] ; and (v) Molecular shields restricting local activity of checkpoint inhibitors. 266 For future research, we propose studies designed to identify novel regulatory molecules that, when targeted, simultaneously enhance anti-tumor immunity yet suppress autoimmunity.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we devised a strategy to combine conventional targeted therapy with immune checkpoint blockade (anti-PD1/PDL1) by a BsAb approach to treat solid tumors. In the BsAb embodiment, the anti-PD1 antibody is directed to the tumor microenvironment by a second antibody targeting a tumor associated antigens expressed in the tumors [29] . The BsAb, anti-PD1 x EGFR BsAb, was constructed by fusion of two anti-PD1 scFv symmetrically to the N-terminus of the heavy chains of cetuximab.…”
Section: Discussionmentioning
confidence: 99%
“…There are in theory several rationales for co-targeting EGFR on tumor cells and PD1 on T cells via a BsAb: 1) accumulating evidence demonstrated that stimulation of EGFR signaling can suppress immune responses and enhance the tumor cell evasion of immune surveillance, including induction of PDL-1 overexpression on the surface of tumor cells, stimulation of VEGF, IL6, IL10 secretion, activation of regulatory T cells (Tregs) and downregulation of T cell chemokines [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] . Inhibition of EGFR signaling in tumor cells, therefore, not only can exert direct antitumor activity but also may create a more favorable anti-tumor immune microenvironment [40 , 46] ; 2) By targeting EGFR-overexpressing tumor cells, anti-PD1 x EGFR BsAb may enhance the antibody localization to specifically target and activate T cells and other immune cells within the tumor microenvironment [29] ; 3) the BsAb simultaneously targeting EGFR on tumor cell surface and PD1 on T cells may likely be able to create direct cell-cell interaction/engagement of the tumor cells and the immune cells, and leads to the formation of immunological synapse, resulting in CD8 + T cell activation and potent tumor cell killing [30 , 47] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, EGFR, as an essential receptor of transforming growth factor alpha, has attracted widespread attention. Previous studies have found that the frequency of oncogenic mutations in the EGFR gene is closely related to the occurrence of melanoma [29][30][31]. In addition, EGFR has been proposed as an important molecular target for the treatment of cancer, which has promoted the development of EGFR pharmacological inhibitors [32,33].…”
Section: Discussionmentioning
confidence: 99%